A method for preparing an ionic hydrogel with a gradient structure, and its product and application

Synthesis of PVA ionic hydrogels with gradient structures through low-temperature directional ion diffusion methods solves the challenges of existing hydrogel sensors in high sensitivity and large-scale detection, achieving higher sensitivity and wide sensing range, suitable for pressure sensors and wearable sensing devices.

CN115181290BActive Publication Date: 2025-04-15NANJING FORESTRY UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210735651.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-27
Publication Date
2025-04-15
Estimated Expiration
2042-06-27

AI Technical Summary

Technical Problem

Existing hydrogel sensors have challenges in high sensitivity and wide range detection, and their mechanical properties cannot meet the requirements of pressure sensors.

Method used

A physically crosslinked PVA ionic hydrogel with a gradient structure was synthesized by low-temperature directional ion diffusion method, and a gradient of dense non-porous structure and porous structure was formed in the gel through diffusion of aqueous sodium chloride solution.

Benefits of technology

It achieves higher sensitivity and wide sensing range, excellent capacitive signal stability, and can effectively monitor weak physiological signals and human movement.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115181290B_ABST
    Figure CN115181290B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing an ionic hydrogel with a gradient structure, a product and an application thereof. The method comprises the following steps: dissolving polyvinyl alcohol in deionized water to prepare a polyvinyl alcohol aqueous solution, pouring the polyvinyl alcohol aqueous solution into an open mold whose bottom is wrapped with a semipermeable membrane at room temperature, placing the mold in a sodium chloride aqueous solution, diffusing the mold at low temperature, placing the obtained gel in deionized water to remove sodium chloride inside the gel, freezing and thawing, and storing the gel to obtain an ionic hydrogel with a gradient structure. The ionic hydrogel has higher sensitivity and a wide sensing range, and excellent capacitance signal stability, and can be used as a reliable wearable sensing device to monitor various weak physiological signals and human body movements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a method for preparing an ionic hydrogel with a gradient structure, a product thereof and an application thereof. Background Art

[0002] Hydrogel is a special soft and wet material with a three-dimensional network structure and high water content, which has a wide range of applications in biomedicine and sensing. In recent years, flexible conductive hydrogel sensors have received great attention in the preparation of medical monitoring equipment, intelligent robots and wearable sensors, because they can mimic the flexibility and sensory properties of human skin by converting various external stimuli into electrical signals. Although hydrogel sensors have made significant progress, it is still challenging to overcome their limitations and achieve high sensitivity and large-range detection at the same time.

[0003] To address this issue, current strategies focus on the structural design and optimization of hydrogels, including the introduction of pyramidal or wrinkled structures to reduce the initial contact area and increase the final contact area during compression. Although these strategies greatly expand the detection range at the same sensitivity, there is still a big gap compared with the sensing ability of human skin. Human skin usually has a sensitive tactile feedback system that can quickly and accurately sense the surrounding environment. However, most of the reported gradient hydrogels used in biological tissue engineering do not have mechanical properties that meet the requirements of pressure sensors. Summary of the invention

[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0005] The invention provides a method for preparing an ionic hydrogel with a gradient structure, which is characterized by comprising the following steps: dissolving polyvinyl alcohol in deionized water to prepare a polyvinyl alcohol aqueous solution, pouring the polyvinyl alcohol aqueous solution into an open mold with a semipermeable membrane wrapped at the bottom at room temperature, placing the mold in a sodium chloride aqueous solution, diffusing the mold at low temperature, placing the obtained gel in deionized water to remove sodium chloride inside the gel, freezing and thawing, and storing the gel to obtain the ionic hydrogel with a gradient structure.

[0006] As a preferred solution of the method for preparing the ionic hydrogel with gradient structure described in the present invention: the step of dissolving polyvinyl alcohol in deionized water is to prepare the polyvinyl alcohol into a 15 wt % polyvinyl alcohol aqueous solution.

[0007] As a preferred solution of the method for preparing the ionic hydrogel with gradient structure described in the present invention: the molecular weight of the polyvinyl alcohol is 105,000.

[0008] As a preferred solution of the method for preparing the ionic hydrogel with gradient structure described in the present invention: the semipermeable membrane has a molecular weight cutoff of 1000Da.

[0009] As a preferred solution of the method for preparing the ionic hydrogel with gradient structure of the present invention: the mass concentration of the sodium chloride aqueous solution is 25wt%.

[0010] As a preferred solution of the method for preparing the ionic hydrogel with gradient structure described in the present invention: the diffusion at low temperature is to diffuse at -15 to -20°C for 8 hours.

[0011] As a preferred solution of the method for preparing the ionic hydrogel with gradient structure described in the present invention: the mold has a size of 30 mm×30 mm×2.5 mm, the volume of the polyvinyl alcohol aqueous solution is 2.25 mL, the volume of the sodium chloride aqueous solution is 25 mL, and the liquid level of the sodium chloride aqueous solution is higher than the liquid level of the polyvinyl alcohol aqueous solution.

[0012] As a preferred solution of the method for preparing the ionic hydrogel with gradient structure described in the present invention: the storage is performed using a 10 wt % lithium chloride solution.

[0013] As another aspect of the present invention, the present invention provides the use of the ionic hydrogel with a gradient structure obtained by the preparation method as a pressure sensor: the ionic hydrogel with a gradient structure is placed between two layers of indium tin oxide poly films to obtain the pressure sensor.

[0014] Beneficial effects of the present invention: A physically cross-linked PVA ion hydrogel with a gradient structure is synthesized by a low-temperature directional ion diffusion method, and the synthesis route is very simple. The gel has a gradient structure along the ion diffusion direction, with a dense non-porous structure at the bottom of the gel and a porous structure at the top. Due to this special gradient structure, the pressure sensor constructed with the gradient gel has higher sensitivity and a wide sensing range, and excellent capacitance signal stability, and can be used as a reliable wearable sensing device to monitor various weak physiological signals and human body movements. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0016] Figure 1 The compressive stress-strain curve and the scanning electron microscope image of the gradient ion gel of Example 1.

[0017] Figure 2 Schematic diagram of the sample sandwich structure pressure sensor of Example 1.

[0018] Figure 3 The cyclic compression stress-strain fatigue test results of the gradient gel of the sample in Example 1.

[0019] Figure 4 The capacitance change (ΔC / C0) of the gradient ion gel under periodic loading pressure of the sample in Example 1.

[0020] Figure 5 ΔC / C0 of the gradient gel sensor when the gel is pressed with different pressures, i.e., light touch (≈10 kPa), medium touch (≈20 kPa) and heavy touch (≈50 kPa), and the inset shows a photograph of the gel sensor pressed with a finger.

[0021] Figure 6 The relative capacitance of the sample of Example 1 changes with time when the index finger is bent at different angles (0°, 30°, 45°, 60° and 90°).

[0022] Figure 7 The relative capacitance changes over time when monitoring the pulse for the sample of Example 1. The inset shows a photograph of the gel sensor as a wearable pulse monitor.

[0023] Figure 8 is the compressive Young's modulus.

[0024] Fig. 9 These are photos of gel diffusing simultaneously at different temperatures for 8 hours.

[0025] Fig.10 The pressure-capacitance response curves of gradient ion gel and homogeneous ion gel.

[0026] Fig.11 This is the gel photo of Control Example 1.

[0027] Fig.12 This is the gel photo of Control Example 2.

[0028] Fig.13 This is the gel photo of Control Example 3. DETAILED DESCRIPTION

[0029] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with specific embodiments.

[0030] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0031] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0032] The preparation method of PVA ion hydrogel with gradient structure, whose microstructure is shown in the scanning electron microscope image, has the structural characteristics that the gel gradually changes from a dense non-porous structure to a porous structure from the bottom to the top, and the pore size at the top is 10-20μm.

[0033] The preparation method of the gradient ion gel pressure sensor in the present invention is as follows: first, polyvinyl alcohol is dissolved in deionized water. After the polyvinyl alcohol is completely dissolved, the sol is poured into a square opening mold, and the bottom is wrapped with a semipermeable membrane. The mold containing the sol is placed in a sodium chloride solution and diffused at low temperature for a period of time. The obtained gel is placed in deionized water to remove the sodium chloride inside the gel, and then a freeze-thaw cycle is performed. Finally, the gel is placed in a lithium chloride solution for storage to obtain a gradient structure gel, specifically:

[0034] In the first step, polyvinyl alcohol 124 (M w =105000) is dissolved in deionized water. After complete dissolution, the sol is poured into a square-opening mold, and the bottom is wrapped with a semipermeable membrane. The mold containing the sol is placed in a sodium chloride solution and diffused at low temperature for a period of time; the second step is to place the obtained gel in deionized water to remove the sodium chloride inside the gel, and then perform a freeze-thaw cycle; the third step is to finally store the gel in a lithium chloride solution to obtain the final gradient ion gel.

[0035] In the first step, the concentration of PVA is 15 wt %, the dissolution temperature is 95° C., the dissolution time is 3 h, and the molecular weight cutoff of the semipermeable membrane is 1000 Da.

[0036] In the first step, 25 mL of a sodium chloride solution with a mass concentration of 25 wt % is prepared for diffusion, the diffusion temperature is -15°C, and the diffusion time is 8 h.

[0037] In the second step, the gel was placed in deionized water for 6 h and then subjected to a freeze-thaw cycle at -15 °C for 8 h.

[0038] In the third step, the frozen-thawed gel was placed in a 10 wt % LiCl solution for storage.

[0039] The gradient ion gel described in the present invention is used as a pressure sensor for detecting pressure. The sensing test utilizes the change in capacitance signal in response to external pressure, and the obtained gradient ion gel is placed between two layers of indium tin oxide poly(ethylene naphthylacetate) (ITO-PEN) films to obtain the gradient ion gel pressure sensor.

[0040] Embodiment 1:

[0041] Preparation of gradient gel: Polyvinyl alcohol 124 (M w =105000) was dissolved in deionized water to prepare a 15wt% polyvinyl alcohol aqueous solution. At room temperature, 2.25mL of the polyvinyl alcohol aqueous solution was poured into a square-opening mold (size: 30mm×30mm×2.5mm) with a semipermeable membrane (molecular weight cutoff: 1000Da) wrapped at the bottom, and the entire mold was placed in 25mL of a sodium chloride aqueous solution with a mass concentration of 25wt%, so that the liquid level of the sodium chloride aqueous solution was slightly higher than the liquid level of the polyvinyl alcohol aqueous solution, and sodium chloride could enter the polyvinyl alcohol solution through the translucent. After immediately being placed at -15°C for 8h of diffusion, the obtained gel was placed in deionized water for 6h to remove the sodium chloride inside the gel, and then a freeze-thaw cycle was performed. Finally, the gel was placed in a lithium chloride solution (10wt%) for storage to obtain a gradient ion gel, and its scanning electron microscope photo is shown as follows: Figure 1 As shown. (a) Compressive stress-strain curves of hydrogels prepared at different diffusion temperatures (25°C, 0°C, –15°C and –20°C) for 8 h. (b) Compressive stress-strain curves of hydrogels with different diffusion times (2h, 4h, 8h and 14h) at –15°C. (c) Cross-sectional SEM images of gradient hydrogels, overview (left) and partial magnification (right); (d) Comparative photos of gradient gels and uniform gels at different set pressures.

[0042] Preparation of gradient gel pressure sensor: The gradient ion gel is placed between two layers of indium tin oxide poly (ethylene glycol naphthylacetate) (ITO-PEN) films and a voltage is applied to obtain a gradient pressure sensor, such as Figure 2 shown.

[0043] Mechanical property test: The gradient ion gel has excellent mechanical properties. The gradient gel was subjected to 1000 compression loading-unloading cycle tests using a mechanical testing machine at an experimental rate of 30 mm / min.

[0044] Gradient gels show excellent elasticity and durability, which are also important parameters in flexible devices. Figure 3It can be seen that after 1000 compression fatigue cycles, the gradient gel maintained its mechanical properties without obvious attenuation (<4.7%).

[0045] Capacitive signal test: To evaluate the sensitivity and detection range of the gradient ion gel sensor, the relative capacitance change with increasing pressure was recorded. The sensitivity of the capacitive pressure sensor is defined as S = δ(ΔC / C0) / δP, where P represents the applied pressure, and C and C0 represent the capacitance with and without applied pressure, respectively. The pressure sensitivity is calculated from Fig.10 It can be seen that the sensitivity of the low pressure area (<100kPa) is as high as 1.09kPa -1 , which is 6.4 times that of the uniform gel. In contrast, the sensitivity in the high pressure region (>100 kPa) is reduced to 0.06 kPa -1 Overall, the gradient gel sensor exhibited excellent pressure sensitivity over the entire pressure region. The excellent performance can be attributed to the large modulus difference of the gel gradient structure.

[0046] Further experiments were conducted to evaluate the responsiveness, repeatability, and reliability of the pressure sensor by measuring the relative capacitance changes under periodic loads of 400Pa, 23kPa, 60kPa, and 180kPa, respectively. Figure 4 It can be found that the gradient gel sensor has a low signal-to-noise ratio and stable continuous pressure responsiveness over a wide load range.

[0047] Stress performance test:

[0048] like Figure 5 As shown, the gradient gel sensor can accurately distinguish between continuous soft touch (≈10 kPa), moderate contact (≈20 kPa), and heavy blow (≈50 kPa), indicating that the sensor can simulate the instantaneous responsiveness of human skin to external stimuli.

[0049] Monitoring human motion and personal health: Gradient gel as a wearable pressure sensing device for finger bending monitoring. In this experiment, we taped the gel to the index finger. Figure 6 As shown in Figure 2, as the bending angle increases from 0° to 90°, the relative capacitance gradually increases, accurately reflecting the angle of finger bending. When the finger bending angle remains unchanged, the capacitance signal is stable. In addition, the gradient gel can be used for pulse detection, where the gradient gel is attached to the wrist of a volunteer. Figure 7 As shown, the pulse sensing output capacitor signal indicates that the pulse rate is 90min -1 , which is within the range of pulse rates of healthy adults. The gradient gel has high sensitivity and instantaneous response, showing great potential in human motion detection and physiological signal monitoring.

[0050] In the present invention, the concentration of sodium chloride has a great influence on the salting-out effect. The salting-out effect of low-concentration sodium chloride solution is poor, and it is difficult to achieve PVA molecular chain entanglement through salting-out. Sodium chloride solution with too high concentration will lead to insignificant difference in gradient modulus, and too high concentration of sodium chloride at low temperature will precipitate due to reduced solubility. Therefore, the effect is not good, and the gradient difference is not obvious. At the same time, too low concentration of PVA will lead to low overall mechanical strength of the gel. Similarly, too high concentration may cause the diffusion rate of sodium chloride to become faster, making it difficult to adjust the gradient distribution of ions, which ultimately leads to insignificant difference in gradient modulus, and the gel strength is too high and is not suitable for the field of flexible sensing.

[0051] In summary, the present invention proposes a method for preparing gradient PVA ion hydrogel by ion directed diffusion in 25wt% NaCl solution under low temperature (-15°C) conditions. The gradient ion hydrogel was successfully constructed through the synergistic effect of freezing and salting-out effects. Due to the porous structure induced by ice crystals, the top of the gradient hydrogel has a lower elastic modulus (about 44.3kPa), while the bottom of the gel has a higher elastic modulus (about 4.9MPa), which is a dense structure caused by the salting-out effect. The gradient gel is assembled into a capacitive pressure sensor with stable capacitance signal and high sensitivity (1.09kPa -1 ), wide detection range (400Pa-0.8MPa), and fast response speed (92ms). In addition, the gradient gel sensor exhibits micro-strain response performance under repeated small compressive strain and water droplets. The excellent capacitance signal stability enables the gel sensor to be used as a highly reliable wearable sensing device to monitor various weak physiological signals and human body movements. This innovative preparation method provides ideas for the design of gradient structures and the development of intelligent bionic materials.

[0052] Research example:

[0053] According to the method of Example 1, after the mold is placed in a sodium chloride aqueous solution, it is diffused for different times (4h, 8h and 24h) at different temperatures (-20℃, -15℃, 0℃ and 25℃). At the diffusion temperatures of -15℃ and -20℃, the compressive stress in the low-pressure area (<100kPa) increases slowly with the increase of strain, while it increases rapidly in the high-pressure area (>100kPa). When the diffusion temperature is 0℃, the compressive stress of the gel increases rapidly in the low-pressure area and slowly in the high-pressure area. This is because ice crystals form slowly at 0℃, and it is difficult for PVA chains to aggregate and crystallize through hydrogen bonds to form a porous structure. Therefore, the structure of the gel is mainly caused by the salting-out effect. The compressive stress-strain curve of the gel prepared at room temperature (25℃) shows a trend similar to that at 0℃, which also proves that the porous structure caused by ice crystals plays a key role in the formation of the gradient structure.

[0054] like Figure 8 As shown, (a) the compressive Young's modulus of the hydrogels (at different temperatures (25°C, 0°C, -15°C and -20°C) with a fixed diffusion time of 8h) in the strain range of 0-10% and 70-80%. (b) The compressive Young's modulus of the hydrogels (at different diffusion times (2h, 4h, 8h and 14h) at -15°C) in the strain range of 0-10% and 70-80%, respectively. As the diffusion temperature decreases, the difference in modulus between the two regions gradually increases and reaches a maximum at -15°C. The corresponding Young's moduli are 44.3 kPa and 4.9 MPa, respectively. For the gels prepared at 0°C and 25°C, the Young's modulus in the strain range of 0-10% is higher than that at -15°C, while the modulus in the strain range of 70-80% is lower. This result is attributed to the fact that rapid ion diffusion is not conducive to the sufficient aggregation of PVA chains at the bottom of the gel. It was further confirmed that ice crystals have an important influence on the formation of the low modulus part of the gel. When the diffusion process was carried out at 25°C, the gel volume shrank by 24%, indicating that rapid ion diffusion causes a strong salting-out effect. Digital photos show that the gel becomes opaque after the diffusion process, while the gel prepared at a lower temperature is almost transparent and maintains its original shape ( Fig. 9 ). Fig. 9 The photographs are of gel diffusion (8 h) at different temperatures (25°C, 0°C, -15°C and -20°C).

[0055] The effect of diffusion time on the hydrogel structure was studied at a fixed temperature of -15°C, and the compressive stress of the hydrogel gradually increased with the increase of diffusion time. This result can be explained by the fact that the extension of diffusion time increases the ion concentration within the gel, and the continuous salting-out effect enhances the mechanical properties of the gel. Comparing the stress-strain curves, it can be found that the 8h curve is more in line with the J-shaped characteristics, which makes the gel more suitable for high-sensitivity sensing in a wide pressure range. The corresponding modulus differences in the strain ranges of 0-10% and 70-80% were calculated. It can be seen that with the increase of diffusion time, the modulus difference gradually increases and reaches a maximum value at 8h. However, further extending the diffusion time by 14h will lead to a decrease in the modulus difference, which is due to the long-term salting-out effect that causes the gel structure to become dense. Therefore, -15°C and 8h were adopted as the optimal diffusion conditions.

[0056] Comparative Example 1:

[0057] Compared with Example 1, sodium chloride was replaced by calcium chloride, and other experimental conditions remained unchanged. The mechanical properties of the obtained gel were weak and there was no obvious difference in gradient modulus, which may be due to the salt dissolution effect of calcium chloride, resulting in weak overall mechanical properties. Fig.11 This is a real photo of the gel.

[0058] Comparative Example 2:

[0059] When the sodium chloride in Example 1 is replaced by sodium sulfate, sodium carbonate or sodium acetate, and other experimental conditions remain unchanged, the obtained gel has high mechanical strength but no significant difference in gradient modulus. Since sodium carbonate has a stronger salting-out effect, it induces rapid entanglement of molecular chains to form a dense molecular chain network structure. This rapid and strong salting-out effect causes a significant shrinkage in the gel volume. It can be seen that such anions with strong salting-out effect are difficult to be used to effectively prepare gradient gels. Fig.12 Actual photographs of gels prepared for the three anionic salts.

[0060] Comparative Example 3:

[0061] Compared with Example 1, PVA was replaced with carboxymethyl cellulose, and other experimental conditions remained unchanged. It was not possible to prepare a carboxymethyl cellulose gel with a gradient structure by diffusion of sodium chloride. Fig.13 shown.

[0062] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A method for preparing an ionic hydrogel with a gradient structure, characterized in that: The method comprises the following steps: dissolving polyvinyl alcohol in deionized water to prepare a polyvinyl alcohol aqueous solution, pouring the polyvinyl alcohol aqueous solution into an open mold with a semipermeable membrane wrapped at the bottom at room temperature, placing the mold in a sodium chloride aqueous solution, diffusing the mold at low temperature, placing the obtained gel in deionized water to remove the sodium chloride inside the gel, freezing and thawing, and storing the gel to obtain an ionic hydrogel with a gradient structure; The step of dissolving the polyvinyl alcohol in deionized water is to prepare the polyvinyl alcohol into a 15-18 wt % polyvinyl alcohol aqueous solution; The polyvinyl alcohol has a molecular weight of 105,000; The semipermeable membrane has a molecular weight cut-off of 1000-1200 Da; The mass concentration of the sodium chloride aqueous solution is 25-30 wt%; The diffusion at low temperature is diffusion at −15 to −20 °C for 8 to 10 hours; The storage is performed by using a 10-12 wt% lithium chloride solution.

2. The method for preparing an ionic hydrogel having a gradient structure according to claim 1, characterized in that: The mold has a size of 30 mm×30 mm×2.5 mm, the volume of the polyvinyl alcohol aqueous solution is 2.25 mL, the volume of the sodium chloride aqueous solution is 25-30 mL, and the liquid level of the sodium chloride aqueous solution is higher than the liquid level of the polyvinyl alcohol aqueous solution.

3. The ionic hydrogel with a gradient structure prepared by the method for preparing an ionic hydrogel with a gradient structure according to claim 1.

4. The use of the ionic hydrogel with a gradient structure prepared by the method for preparing the ionic hydrogel with a gradient structure according to claim 1 as a pressure sensor, characterized in that: The ionic hydrogel with a gradient structure is placed between two layers of indium tin oxide poly films to obtain the pressure sensor.

Citation Information

Patent Citations

  • High-strength strain-sensitive polyvinyl alcohol ion hydrogel sensing material, and preparation method and application thereof

    CN110256697A